Plasma Lipidomics Profiles After a Diet Characterized by Whole Grains Compared to a Diet High in Refined Grains and Added Sugars (FS03-07-19). (13th June 2019) - Moghadam, Sepideh Dibay; Navarro, Sandi; Shojaie, Ali; Randolph, Timothy; Bettcher, Lisa; Le, Cynthia; Hullar, Meredith; Kratz, Mario; Neuhouser, Marian; Lampe, Paul; Raftery, Daniel; Lampe, Johanna
Abstract: Objectives: Dietary patterns high in fiber from sources including whole grains, legumes, fruits, vegetables, nuts and seeds, are associated with lower risk of chronic disease, such as cardiovascular disease and cancer. We investigated how plasma lipidomics profiles differed between a diet high in whole grains (WG) versus a diet high in refined grains and added sugars (RG). Methods: Using a randomized, crossover, controlled feeding study, 80 healthy participants (n = 40 men, n = 40 women, 40 normal weight, 40 overweight/obese), 18–45 y, were randomized to receive either a WG or RG diet for 28 days. After a 28-day washout period where participants resumed their habitual diet, they crossed over to the other diet. Targeted, differential mobility mass spectrometry was performed on fasting plasma samples collected at the baseline and end of each diet period and quantified the concentrations of 863 lipids from 13 classes. Paired t-tests and pairwise partial least squares-discriminant analysis (PLS-DA) were used to evaluate differences in lipid profiles between the two diets. Results: At a class level, only ceramides were significantly different when comparing the two diets. After removing lipid species with > 20% missing values or CVs < 25%, 606 were retained for species analysis. Sixty-seven lipid species were significantly different between diets at day 28 (FDR < 0.05): 38 of 414 detected triglycerides, 9 of 59 phosphatidylethanolamines, 9 of 63 phosphatidylcholines, 4 of 22 cholesterol esters, 3 of 11 sphingomyelins, 2 of 13 lysophosphatidylcholines, and 1 of 5 ceramides. The majority of significant lipids were higher in plasma after the WG diet. PLSDA analysis showed the first and second components explaining 49% and 8.4%, respectively. Based on the selected components, lipidomic profiles showed fair separation for the two groups of diet. R2 values were 0.07 and 0.43, and Q2 values were -0.03 and 0.04 for components 1 and 2, respectively. Conclusions: Higher concentrations of some lipid species such as cholesterol ester 12:0, a carrier of high-density lipoprotein, could indicate a favorable shift in lipid profiles. Further investigation using more complex models are being conducted. Funding Sources: National Cancer Institute - National Institutes of Health.